Android phone : remote control for Nikon camera II - Pabeda, Philips (2012)
In recent day, population of Digital Single Lens Reflex (DSLR) type camera increases significantly and becomes very popular device for either amateur or professional photographer. The camera is usually easy to be used and mostly gives satisfactory results if a proper setting is provided. Unfortunately the system is still utilized relatively small LCD screen to pre evaluation of the result.